Reaction Kinetics of Potassium Sulfate Formation from Bleaching Earth Liquid Waste and Potassium Hydroxide - Adinda Fatin Hamama; Gabriel Firgiane Cinta Sari; Caecilia Pujiastuti; Erman Adi Saputro; Ketut Sumada (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study examines the kinetics of potassium sulfate (K2SO4) formation from industrial liquid waste generated by bleaching earth. The objective is to evaluate the effects of temperature and reaction time on the conversion rate of sulfuric acid, determine the reaction order, and calculate the activation energy. The process involves reacting the diluted acid-rich liquid waste with analytical-grade potassium hydroxide (KOH) under constant stirring at temperatures of 50–70°C for 20–40 minutes. The results show that conversion increases with higher temperature and longer reaction time, reaching an optimum conversion (XA) of 96.22% at 70°C for 40 minutes. Kinetic analysis indicates that the reaction follows a second order model based on the highest coefficient of determination (R2). The calculated activation energy (Ea) is 8580.048 J/mol with a frequency factor (k0) of 367.0784, expressed in the rate constant equation, adhering to the Arrhenius model (R2 = 0.844) despite slight experimental deviations. These findings highlight the potential use of bleaching earth liquid waste as a raw material for potassium sulfate production and provide insight into its reaction kinetics. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Actio